1987
DOI: 10.1246/cl.1987.2299
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Preparation of Pure Dialkylmagnesium from a Grignard Reagent

Abstract: Dimethyl ether of acyclic polyethers, Me(OCH2CH2)nOMe, predominantly coordinated to MgX2 in an ether solution of Grignard reagent and the MgX2 adduct was removed as a precipitate. Consequently, an ethereal solution of pure R2Mg was obtained in reasonable yield. This method is more convenient than those known general.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…All solvents were stored in a glovebox. Compound MCM-41 (M1), [18] 1, [16] 2 [16] 3, [17c] and MgMe 2 [43] were synthesized according to literature procedures. TEA was purchased from ABCR and used as received.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…All solvents were stored in a glovebox. Compound MCM-41 (M1), [18] 1, [16] 2 [16] 3, [17c] and MgMe 2 [43] were synthesized according to literature procedures. TEA was purchased from ABCR and used as received.…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Although we expected the intended bromine-magnesium exchange to proceed relatively fast, [21] exposing 8 a in THF solution to essentially the same conditions as 5, [22] that is to slight excesses both of MgHal 2 -free iPr 2 Mg [23] and the lithium salt (Li-11) of the monomethyl ether (11) [24] of (S)-BINOL (À40 8C, 20 min) we obtained none of the expected diaryl sulfoxide 7 a but 25 % isopropyl phenyl sulfoxide (+)-(R)-9 b and 57 % bromoisopropyl phenyl sulfoxide (+)-(R)-9 a (Scheme 1, middle). This suggested that a selective sulfoxide-magnesium exchange [25] had occurred first (!…”
mentioning
confidence: 99%
“…[b] Conditions: 11 (1.5 equiv), THF, nBuLi (1.5 equiv), 0 8C, 10 min; 22 8C, 10 min; iPr 2 Mg [23] (1. symmetrizes dibromo sulfoxide 8 a as well (! 7 a + iPrBr).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…All materials were purchased from Aldrich chemical company, Acros Organics, or Fisher Scientific, with the exception of dimethylmagnesium and diethylmagnesium, which were prepared by the method of Saheki et al [24]. Diethyl ether was dried by distillation under N 2 from sodium/benzophenone ketyl.…”
Section: Methodsmentioning
confidence: 99%